Digitalisasi Pendaftaran Layanan Eazy Passport Berbasis Web pada Kantor Imigrasi Kelas I Non TPI Pati - Adinda Bintang Oktavia; Supriyono (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Immigration public services require digital innovation to improve efficiency, accuracy, and service transparency. The Eazy Passport service at the Class I Non-TPI Immigration Office of Pati has been managed through a manual registration process using formal letters, resulting in administrative inefficiencies, data entry errors, and difficulties in service scheduling. This community service activity aims to design and implement an integrated web-based registration and scheduling system for the Eazy Passport service. The implementation stages included needs analysis, system design, web application development, and system testing. The results show that the developed system simplifies the registration process for applicants, reduces administrative workload for immigration officers, improves data organization, and supports more structured and transparent service scheduling. The system provides a practical digital solution that contributes to enhancing the quality and efficiency of immigration public services.